2017
DOI: 10.1039/c6fo01738j
|View full text |Cite
|
Sign up to set email alerts
|

Olive leaf extract concentrated in hydroxytyrosol attenuates protein carbonylation and the formation of advanced glycation end products in a hepatic cell line (HepG2)

Abstract: Glycation takes place both at the cellular level and at the extracellular matrix level and generates, consequently, advanced glycation end-products (AGEs) associated with chronic diseases and the aging process. Two olive leaf extracts concentrated in (i) oleuropein (OLE-A; 93.9 mg oleuropein g) and (ii) hydroxytyrosol (OLE-B; 54.5 mg hydroxytyrosol g) were evaluated according to their antiglycative and antioxidant capacity in vitro. OLE-B exerted the highest anti-AGE effect in different glycation models (IC: 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
2
14
1
Order By: Relevance
“…Catechins act as a free radical scavenger and prevent lipid peroxidation [177,196]. Authors have also shown a protective role against the oxidation-induced damage in erythrocytes in type 2 diabetes patients [197].…”
Section: Use Of Natural Compounds As Therapeutic Strategiesmentioning
confidence: 99%
“…Catechins act as a free radical scavenger and prevent lipid peroxidation [177,196]. Authors have also shown a protective role against the oxidation-induced damage in erythrocytes in type 2 diabetes patients [197].…”
Section: Use Of Natural Compounds As Therapeutic Strategiesmentioning
confidence: 99%
“…Additionally, previous research showed that the olive leaf extract concentrated in hydroxytyrosol had higher antiglycative and antioxidant activity than the olive leaf extract concentrated in oleuropein. 38 Therefore, increasing the hydroxytyrosol content of olive leaf tea could potentially increase its health benefits. Briante et al 39 explored using recombinant β-glucosidase immobilized in a chitosan support to produce hydroxytyrosol from olive leaf extract on an industrial scale.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, sulforaphane was able to counteract oxidative stress and to increase intracellular GSH levels and the expression, and activity, of glyoxalase 1 [ 236 , 237 ]. Bioactive substances from Olea europaea, such as oleocanthal and hydroxytyrosol, are able to counteract the glycation processes [ 238 , 239 ]; moreover, oleocanthal treatment improves GSH intracellular content and counteracts oxidative stress in neuron-like cell culture [ 240 ]. Recently, Angeloni et al analysed the relationship between oleocanthal and AD suggesting that, besides its effects to interfere with tau protein hyperphosphorylation and aggregation and its ability to induce A β efflux and clearance, it might counteract AD's progression by reducing glycation in the brain, thanks to its positive effect on the GSH level, and to its ability to decrease oxidative stress [ 241 ].…”
Section: Advanced Glycation Endproducts Mediated Neurotoxicity Andmentioning
confidence: 99%